KEPEMIMPINAN VISIONER KEPALA SEKOLAH, BUDAYA KERJA DAN MOTIVASI BERPRESTASI GURU PENGARUHNYA TERHADAP KINERJA GURU SD PENGGERAK DI KABUPATEN ACEH BARAT - Harizal, Harizal; Marwan, Marwan; Bahri, Saiful; Konadi, Win (IndOmera, 2024)
Research to determine the influence of the principal's visionary leadership factors, school culture and teacher achievement motivation on teacher performance. Associative type of quantitative descriptive research method. By using a multiple regression analysis approach. The research was conducted at 8 driving elementary schools in West Aceh Regency. The research results found (a). The level of achievement of the school principal's visionary leadership has reached 93.12%, the level of achievement of school culture that is appropriate and implemented jointly has reached 86.42%. Meanwhile, the principal's assessment stated that teacher achievement motivation was in the very good category, reaching 93.62%, and the teacher's performance level reached 92.29% of ideal expectations. (b) The results of multiple regression analysis conclude that the principal's visionary leadership, school culture and teacher achievement motivation partially have a positive effect on performance, (c). Based on correlation and determination analysis, it is proven that there is a very close relationship and the three factors are R = 0.764. And based on the coefficient of determination, the contribution of the principal's visionary leadership, school culture and teacher achievement motivation to teacher performance is 58.4%